2016
DOI: 10.1021/acs.jpca.6b05735
|View full text |Cite
|
Sign up to set email alerts
|

DFT Calculations on the Mechanism of Transition-Metal-Catalyzed Reaction of Diazo Compounds with Phenols: O–H Insertion versus C–H Insertion

Abstract: The reaction of diazo compounds with transition-metal carbenes is an efficient way to achieve the functionalization of chemical bonds in organic molecules, especially for the C-H and O-H bonds. However, the selective mechanisms of C-H and O-H bond insertions by various metal carbenes such as Rh and Cu complexes are not quite clear. In this work, we performed a comprehensively theoretical investigation of the phenol C-H and O-H bonds inserted by Rh and Cu carbenes by using DFT calculations. The calculated resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 56 publications
2
25
0
Order By: Relevance
“…The diverse carbene-related transformations highlight the indispensable role of carbene in organic synthesis, which also implies that the contributions from computational studies are highly appreciated. , Previous computational studies of metal carbene-mediated X–H insertion (X = C, N, O, etc. ) and olefin metathesis have shown that theoretical calculations can enable a better mechanistic understanding of carbene chemistry. A summary of recent advances in theoretical studies would provide critical guidance for metal carbene formation and enlighten the rational design of new metal carbene transformation reactions. This account mainly focuses on our recent computational studies of the transition-metal-catalyzed carbene transformation with nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
“…The diverse carbene-related transformations highlight the indispensable role of carbene in organic synthesis, which also implies that the contributions from computational studies are highly appreciated. , Previous computational studies of metal carbene-mediated X–H insertion (X = C, N, O, etc. ) and olefin metathesis have shown that theoretical calculations can enable a better mechanistic understanding of carbene chemistry. A summary of recent advances in theoretical studies would provide critical guidance for metal carbene formation and enlighten the rational design of new metal carbene transformation reactions. This account mainly focuses on our recent computational studies of the transition-metal-catalyzed carbene transformation with nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Them echanisms of OÀHi nsertion of diazo compounds with either rhodium or copper as catalysts have been previously studied in detail with DFT calculations. [22] For comparison, DFT studies with O À Hinsertion have also been investigated for the current reaction system. In Figure 1, calculations show that in the O À Hi nsertion process,n ucle-…”
Section: Zuschriftenmentioning
confidence: 99%
“…Then formation of the copper dissociated O-3 from O-2 is endergonic by 11.4 kcal mol À1 .S ubsequent [1,3] proton shift via TS3,assisted by 1k,has an energy barrier of 33.2 kcal mol À1 .T hus,t he overall energy barrier of this pathway is as high as 44.4 kcal mol À1 ,i ndicating that the metal-free [1,3] proton shift pathway is unlikely,a nd is consistent with the study by Yu and co-workers. [22] Alternatively, O-2 can be transferred into O-4 with the oxygen atom coordinated to the copper, and is endergonic by only 5.3 kcal mol À1 .T he following cyclopropanol-assisted [1,3] proton shift via TS4 leads to the OÀHinsertion product 4ka,crossing an overall energy barrier of 29.4 kcal mol À1 .…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Further comprehensive examination of the reaction conditions revealed that the addition of 20 mol % of water gave asatisfactory result (entries 15,16). [24] Therefore, the following experiments were performed to obtain mechanistic information. a-Aryl-a-diazoacetates 1b and 1c with electron-donating substituents were applicable in this OÀHi nsertion, affording the corresponding products 3ba, 3ca in 81 %y ields with high enantioselectivities (94:6, 91:9 e.r., respectively).…”
mentioning
confidence: 99%
“…[22] While detailed mechanisms of thea symmetric carbene insertion into OÀHb ond of water have been investigated, [23] the reaction process of an asymmetric insertion into phenol has not been studied. [24] Therefore, the following experiments were performed to obtain mechanistic information. Reaction in the presenceo fa lkyne 4,i nstead of using phenol, gave ac yclopropene 5 (Eqn.…”
mentioning
confidence: 99%